IMPROVING IMMUNITY SYSTEM WITH JAMU DURING COVID-19 VIRUS PANDEMIC - Maria Heviyanti; Cut Mulyani; Muhammad Muaz Munauwwar (LPPM dan PM Universitas Samudra, 2021)
Global epidemic indicates the Covid-19 infection that is easily spreads to all countries in the world. In this situation, food becomes an important issue that needs special attention. Farmers who are the prime movers in improving food production must have a good immunity as a defense mechanism for farmers. Suka Jadi villages, Banda Mulia District, Aceh Tamiang Regency are the villages where most of the population is farmers. During pandemic, farmers in Suka Jadi village continued to carry out agricultural activities as usual without health protocol. This condition is very worrying because the spread of this virus can occur quickly and widely, so it is possible that farmers can be infected by this virus. The goals of community services to provide an information to the public about the dangers of virus Covid-19 virus and increase immunity by consuming jamu herbal as a natural imunomodulator. The implementation method used is socialization, demonstration of making the herbal ginger and turmeric herbs, and training. This service activity has been able to change the mindset and knowledge of framers about the negative impact of infection and spread of covid-19, the importance of maintaining health by consuming natural imunomodulators such as jamu, and the peasant community has been able to innovate in making herbal jamu in a various kinds of product.